2014
DOI: 10.1186/scrt441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enamel matrix derivative on the proliferation and osteogenic differentiation of human gingival mesenchymal stem cells

Abstract: IntroductionGingiva-derived mesenchymal stem cells (GMSCs) have recently been harvested and applied for rebuilding lost periodontal tissue. Enamel matrix derivative (EMD) has been used for periodontal regeneration and the formation of new cementum with inserting collagen fibers; however, alveolar bone formation is minimal. Recently, EMD has been shown to enhance the proliferation and mineralization of human bone marrow mesenchymal stem cells. Because the gingival flap is the major component to cover the surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
(47 reference statements)
5
27
0
Order By: Relevance
“…Regarding MSCs/GCs, how to improve their differentiation should be further investigated. Certain factors, coculture systems and bioengineered scaffolds could be considered. Developing strategies to prevent senescence is a key issue for MSCs/PDLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MSCs/GCs, how to improve their differentiation should be further investigated. Certain factors, coculture systems and bioengineered scaffolds could be considered. Developing strategies to prevent senescence is a key issue for MSCs/PDLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Human GMSCs are homogenous, not tumorigenic [97], and easy to be isolated [98] and display stable phenotype. The most significant advantage of human GMSCs is without any ethical problems in clinical application [99].…”
Section: Mscs Derived From Other Tissuesmentioning
confidence: 99%
“…Furthermore, GMSC isolated from inflamed tissues demonstrate similar multilineage differentiation potential as compared to those retrieved from healthy tissue [59] . As well, investigators have found that GMSC are non-tumorigenic and maintain normal karyotype and telomerase activity [33,60] . Multiple studies have demonstrated that GMSC tend to proliferate at a higher rate than either PDLSC or BMSC [7,33,61] .…”
Section: Profile and Identitymentioning
confidence: 99%
“…Wu et al examined the use of enamel matrix derivative (EMD) treatment to promote GMSC proliferation and osteodifferentiation, finding a dose dependent increase in Runx2, Alp and Ocn expression with EMD treatment [60] . Conversely, GMSC cultured in adipogenic medium express PPARγ-2 [7] and form lipid globules characteristic of adipogenic differentiation [57] .…”
Section: Profile and Identitymentioning
confidence: 99%